Transforming Teaching with ICT Using the Flipped Classroom Approach: Dealing with COVID-19 Pandemic - Aidoo Benjamin; Macdonald Marey Allyson; Vesterinen Veli-Matti; Pétursdóttir Svava; Gísladóttir Berglind (MDPI, 2025)
During the COVID-19 pandemic, educators changed their pedagogic practices, developed new teaching sequences, and blended learning approaches such as the flipped classroom. Claims have been made that the flipped classroom influences student motivation, enhances active engagement and class participation, and improves academic performance. Three teacher educators were invited to develop flipped instructional materials for chemistry teacher education. The materials included course plans, online videos, tasks, teaching, and online and face-to-face instruction learning sequences. This study examined opportunities and barriers to using the flipped classroom approach for chemistry teaching. Teacher educators were interviewed before and after running the course using the developed instructional materials. The interviews were then analyzed to identify the teachers' rationale, the opportunities, and the challenges of using the flipped classroom. Teacher educators found that integrating technology into their classrooms can enhance their ICT skills and that of their students. Educators believed flipped instructions could promote student-centered learning where students take responsibility for their learning, where and when it is most convenient. The teacher educators perceived that the approach helped students take an active role in their learning and enhance their participation. They also felt that it improved academic performance. Teacher educators also noted that their workload was reduced, and they had more time to interact with students. Some barriers and challenges were recognized as well. In the interviews, teacher educators described how ICT competencies and inadequate ICT infrastructures, such as poor internet connectivity and lack of ICT equipment, limited the use of the flipped classroom approach. The study provides suggestions for future research that can contribute to understanding the practical application of the flipped classroom approach.